Green chemistry & chemical stewardship certificate program: a novel, interdisciplinary approach to green chemistry and environmental health education. Issue 2 (3rd April 2019) - Lasker, Grace A.; Mellor, Karolina E.; Simcox, Nancy J.
ABSTRACT: The Green Chemistry & Chemical Stewardship Certificate Program was designed using the Community of Inquiry (COI) model as a framework for developing curriculum that engages students across the entire program to meet interdisciplinary, professional development program outcomes. The COI framework allows faculty and course developers to develop courses that consider cognitive, social, and teaching presence as equal components of successful learning experiences. In this program, students focus on systems thinking around green chemistry, business, environmental health, chemical alternative assessment tools, and social and environmental justice. They complete a capstone project that identifies a particular environmental or human health issue associated with a chemical and suggest suitable substitutions that are less harmful but equally effective. This paper describes the program's curriculum, partnerships, delivery modalities, and student feedback as a framework developing professional development opportunities that offer a rich interdisciplinary experience for learners. GRAPHICAL ABSTRACT: